Correlation of Ethnobotanical Knowledge with Students’ Environmental Concern Attitude at SMP PGRI 2 Denpasar - Ratnani, Dewa Ayu Sri; Maduriana, I Made (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the correlation between ethnobotanical knowledge and environmental awareness among students at SMP PGRI 2 Denpasar. The study was conducted at SMP PGRI 2 Denpasar. This study is an ex post facto correlational study. The quantitative research method used was simple random sampling to select respondents through questionnaires. Data were analyzed using the Pearson product-moment correlation coefficient and simple linear regression. The results show that the correlation between students’ level of ethnobotanical knowledge and their environmental care attitudes is strong, and the results of the regression analysis show a significance value. This indicates a strong relationship between the level of ethnobotanical knowledge and students' attitudes toward environmental care at SMP PGRI 2 Denpasar. The results of this study indicate a highly significant correlation between ethnobotanical knowledge and environmental awareness. This suggests that the better students' ethnobotanical knowledge, the greater their environmental awareness.